Gene discovery in the developing xylem tissue of a tropical timber tree species: Neolamarckia cadamba (Roxb.) Bosser (kelampayan) - Shek-Ling, Pang; Wei-Seng, Ho; M.N., Mat Isa; Julaihi, Abdullah (Springer-Verlag Berlin Heidelberg, 2015)
A complementary DNA (cDNA) library was constructed from the developing xylem tissues of Neolamarckia cadamba. A total of 10,368 single-pass sequences was generated through high-throughput 5′-expressed sequence tag (EST) sequencing of the cDNA clones, and 6622 highquality ESTs were obtained after removing the low-quality sequences; this gave approximately 3.17 Mb of data. Clustering of the high-quality ESTs revealed 4728 unigenes, consisting of 2100 consensus and 2628 singletons. A total of 2405 ESTs were successfully annotated with 7753 gene ontology (GO) terms that distributed among three main GO categories, which were biological processes (2333), molecular function (3056) and cellular component (2364). Simple sequence repeat (SSR) mining revealed that the frequency of SSR in the N. cadamba EST database (NcbdEST) was 3.3 %, with the GCT/AGC motif being the most abundant repeat motif. The most abundant transcript with known function found in this database was 60S ribosomal protein followed by 40S ribosomal protein. Some of the important genes involved in xylogenesis and lignin biosynthesis were found in NcdbEST; these include tubulin genes, cellulose synthase (CesA), xyloglucan endotransglycosylase (XET), arabinogalactan, cinnamate 4-hydroxylase (C4H), caffeoylcoenzyme A O-methyltransferase (CCoAOMT) and peroxidase. The data obtained from this study will provide a powerful means for identifying mechanisms controlling wood formation pathways of kelampayan and supplymany new cloned genes for future endeavours to modify wood and fibre properties.